Decolonizing Digital Governance: English, Language Accessibility, and Citizen Engagement in Sri Lanka - Abdul Razak, A. (University of Jaffna, 2025)
This study explores the relationship between language accessibility and citizen engagement within Sri Lanka’s digital governance framework, focusing on the role of English in shaping public access to e-government services. As digital technologies and e-government initiatives become increasingly prominent in Sri Lanka, issues surrounding language barriers and the post colonial legacy of English in governance have emerged as critical concerns. Despite the rise of digital governance, many citizens, especially those who do not speak English encounter challenges in accessing government services and information. This research examines how Sri Lanka’s colonial history, with English as the official administrative language, continues to influence the inclusivity and effectiveness of digital governance platforms. Adopting a qualitative research approach, this study combines a literature review and semi-structured interviews to analyze the current state of digital governance in Sri Lanka. The literature review draws upon historical accounts, policy documents, and academic publications to assess the enduring impact of English on governance and the digital divide. Semi-structured interviews with key stakeholders, including government officials, ICT professionals, and citizens, will be conducted to explore their experiences with digital services and identify language-related barriers to engagement. The study particularly emphasizes the participation of marginalized groups, such as Sinhala- and Tamil-speaking citizens, in digital governance. The research is framed by the belief that digital governance can be a tool for decolonization, addressing language inequalities embedded in post-colonial governance systems. By analyzing how English continues to dominate e-government platforms, this research seeks to highlight the need for inclusive policy reforms that reflect Sri Lanka’s linguistic diversity. Key themes include the digital divide, language policy in public administration, and the role of e-government platforms in enhancing citizen engagement. Findings offer a comprehensive understanding of the challenges faced by language minorities in accessing digital services and provide actionable recommendations for improving language inclusivity. This study contributes to the broader conversation on decolonizing public administration in post-colonial states and aims to promote equitable participation in the digital era. Through inclusive policy reforms, Sri Lanka’s e-government initiatives can better align with the principles of social justice and inclusive development. This study explores the relationship between language accessibility and citizen engagement within Sri Lanka’s digital governance framework, focusing on the role of English in shaping public access to e-government services. As digital technologies and e-government initiatives become increasingly prominent in Sri Lanka, issues surrounding language barriers and the post-colonial legacy of English in governance have emerged as critical concerns. Despite the rise of digital governance, many citizens - especially those who do not speak English-encounter challenges in accessing government services and information. This research examines how Sri Lanka’s colonial history, with English as the official administrative language, continues to influence the inclusivity and effectiveness of digital governance platforms. Adopting a qualitative research approach, this study combines a literature review and semi-structured interviews to analyze the current state of digital governance in Sri Lanka. The literature review draws upon historical accounts, policy documents, and academic publications to assess the enduring impact of English on governance and the digital divide. Semi-structured interviews with key stakeholders, including government officials, ICT professionals, and citizens, were conducted to explore their experiences with digital services and identify language-related barriers to engagement. The study particularly emphasizes the participation of marginalized groups, such as Sinhala- and Tamil-speaking citizens, in digital governance. The research is framed by the belief that digital governance can be a tool for decolonization, addressing language inequalities embedded in post-colonial governance systems. By analyzing how English continues to dominate e-government platforms, this research seeks to highlight the need for inclusive policy reforms that reflect Sri Lanka’s linguistic diversity. Key themes include the digital divide, language policy in public administration, and the role of e-government platforms in enhancing citizen engagement. The findings offer a comprehensive understanding of the challenges faced by language minorities in accessing digital services and provide actionable recommendations for improving language inclusivity. This study contributes to the broader conversation on decolonizing public administration in post colonial states and aims to promote equitable participation in the digital era. Through inclusive policy reforms, Sri Lanka’s e-government initiatives can better align with the principles of social justice and inclusive development.
Keywords: Digital governance; Language accessibility; E-government services; Citizen engagement; Post-Colonial legacy